PREFIKSASI DALAM LIRIK LAGU BUKTI DAN SELAMAT TINGGAL PADA ALBUM SURAT CINTA UNTUK STARLA - Mulyana, Devina; Hasanah, Elsa Kholifatul; Ulfah, Fadilla; Nurjam’an , Muhammad Ichsan (ISOLEK: Jurnal Pendidikan, Pengajaran, Bahasa, dan Sastra, 2025)
This research is motivated by the importance of understanding morphological processes, especially affixation, which plays a role in the formation and meaning of words in Indonesian. Amidst the rise of language errors among teenagers due to the influence of popular language, examples of the use of correct language forms are needed. This study aims to describe the prefix forms in two Virgoun songs in the album Surat Cinta untuk Starla, namely "Bukti" and "Selamat Tinggal." The study uses a qualitative descriptive method with content analysis of the lyrics to identify the types of prefixes and their grammatical meanings. The results show that the song "Bukti" contains 8 prefix forms, consisting of the prefixes ber-, mem-, men-, and ter-, with the highest frequency in the prefixes ber- and ter-. The song "Selamat Tinggal" contains 20 prefix data in the form of the prefixes ber-, me-, ku-, and ter-, with the dominance of the prefixes ber- and me-. In general, the use of prefixes in both songs clarifies the actions, states and emotional expressions that the songwriters want to convey. These findings can be utilized in Indonesian language learning as teaching materials to introduce the word formation process through examples that are relevant and close to students' lives.